Pembuatan Perpustakaan Genom Kedelai (Glycine max (L.) Merrill) Kultivar Lumut di dalam Fag Lambda - Suharsono Suharsono (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
Genomic library of soybean cv. Lumut had been constructed in l phage vector. Partial digestion of total DNA by 0.014 units Sau3AI per mg DNA at 37oC for 30 minutes gave long fragment DNA. Ligation between insert DNA and l vector with molarity ratio of insert DNA to l vector = 2.9 : 1 followed by phage packaging, resulted in the titer of 2.8x104 to 3.6x105 pfu for 0.5 mg insert plant DNA. Among them, 60 to 91% were recombinants depending on packaging extract protein. By using 1 mg insert plant DNA and packaging extract protein from Stratagene, we obtained 6.6x105 pfu recombinant. Since the length of insert DNAs in l recombinant phages were 15 kb in average and the genome size of diploid soybean was 2.23x106 kb and 90% of the genom was present in 2 copies, then the genomic library constructed had contained all genome of soybean cv. Lumut.